Whole-body vibration exposure among tractor drivers. Issue 3 (11th May 2019) - Singh, Amandeep; Singh, Lakhwinder Pal; Singh, Sarbjit; Singh, Harwinder
A total of 450 experimental runs were performed at three speed levels, i.e., 5.6, 7.4 and 9.3 m/s as well as three sitting postures, i.e., lean forwards (LF), vertical erect with no back rest (VE-NB) and lean with back rest (L-WB). Majority of vibration levels were exceeding ISO 2631-1 1997 exposure action value. Vibration transmission was highest for posture LF followed by VE-NB and L-WB at 7.4 and 9.3 m/s, whereas VE-NB at 5.6 m/s followed by LF and L-WB. Subjective comfort responses are significant at 5% level for neck, shoulder and lower back with mean daily exposure levels. 1/3rd octave band showed dominant frequencies of 3.15 and 4 Hz that could affect health and safety of drivers due to existing natural frequencies of various body parts. It is recommended that tractors need more design efforts to damp vibration transmission along z axis so as to enhance ride comfort level.